Financial fairness and conditional indexation. Issue 8 (14th September 2017) - Kleinow, Torsten; Schumacher, Johannes M.
Abstract : Collective pension contracts can generate advantages for their participants by implementing forms of risk sharing. To ensure the continuity of a collective scheme, it has to be monitored whether the contracts offered to participants are financially fair in terms of their market value. When risk sharing is implemented by means of optionalities such as conditional indexation, the analysis of financial fairness is not straightforward. In this paper, we use a stylised overlapping generations model to study financial fairness for a conditional indexation scheme. We find that financial fairness for all participants at all times is not feasible within a scheme of this type, unless the nature of indexation is such that the scheme is reduced to DC. However, financial fairness for incoming generations at the moment of entry can be realised. We show how to compute the fair contribution rate as a function of the current nominal asset/liability ratio for a given level of nominal entitlements. At low levels of the ratio, the fair contribution for incoming generations is also relatively low; nevertheless, the joining of a new generation still has a positive effect on the asset/liability ratio.